![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
化简cos^8 -sin^8
1个回答
展开全部
cos^8x -sin^8x
=(cos^4x +sin^4x)(cos^4x -sin^4x)
=[(cos^2x +sin^2x)^2-2cos^2x sin^2x](cos^2x +sin^2x)(cos^2x -sin^2x)
=(1-2cos^2x sin^2x)(cos^2x -sin^2x)
=[1-1/2sin^2(2x)]*cos4x
=[1-1/4(1-cos4x )]*cos4x
=(3/4+1/4cos4x )*cos4x
=1/4*cos^2(4x )+3/4*cos4x
=(cos^4x +sin^4x)(cos^4x -sin^4x)
=[(cos^2x +sin^2x)^2-2cos^2x sin^2x](cos^2x +sin^2x)(cos^2x -sin^2x)
=(1-2cos^2x sin^2x)(cos^2x -sin^2x)
=[1-1/2sin^2(2x)]*cos4x
=[1-1/4(1-cos4x )]*cos4x
=(3/4+1/4cos4x )*cos4x
=1/4*cos^2(4x )+3/4*cos4x
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询